The future of the Sultanate of Oman after Sultan Qaboos - Prof. Jassim Younis Alhariri (The college of law and political science journal, 2024)
The above book is written by Prof. Dr. Jassim Younis Al-Hariri, Professor of Political Science and International Relations, and an accredited international expert in Gulf affairs, and a lecturer in the Department of Political Science at Sadr College Iraq Ahlia University. He researched and studied an important stage of the political life of the Sultanate of Oman before and after Sultan Qaboos, Sultan Oman The author says ((I was attracted by some opinions that say that the Sultanate of Oman is the Switzerland of the East, but some of them resemble the Omani capital Muscat in Geneva, and these opinions confirm that the reason for This analogy is not because the Sultanate owns Oman international banks, balances, or reserves in billions, but because it has a neutral position that followed the path of Sultan Qaboos since he took power in 1970.It seems that this (Omani neutrality) made it set itself a factor of approximation within the Gulf house, and between the Gulf countries and their neighbors, and has given a distinct position to the Sultanate Oman its distinguished relationship with Iran, and these positions may contradict some of the positions of the Gulf Cooperation Council countries such as the Kingdom of Saudi Arabia Arabic which is characterized by On the neutrality of the Sultanate of Oman from the Yemeni-Saudi war and its impact on the Omani political scene, the author says ((When the so-called (Decisive Storm) began on March 26, 2015 under the leadership of Saudi Arabia against the Houthis in Yemen, the Sultanate did not participate in that alliance. The important thing is that the Sultanate of Oman succeeded in building an internal experience, based on the balance between its ethnic and sectarian components, in parallel with the regional powers that have extensions within the Sultanate. Indeed, its foreign policy did not move throughout that period according to sectarian considerations, but according to political, economic, and geopolitical considerations.